2019
DOI: 10.1111/bcp.13991
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear pharmacokinetics of rituximab in non‐Hodgkin lymphomas: A pilot study

Abstract: Aims Rituximab is an anti‐CD20 monoclonal antibody approved in non‐Hodgkin lymphoma (NHL). This study aimed to assess the relationship between antigen mass and nonlinear pharmacokinetics of rituximab in NHL patients. Methods In a retrospective cohort of 25 NHL patients treated with rituximab, antigen mass was assessed at baseline by measuring metabolic tumour volume (MTV) by positron emission tomography. Rituximab pharmacokinetics was described using a semimechanistic 2‐compartment model including a latent tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
1
13
2
Order By: Relevance
“…Recent PK studies have reported that tumor burden in uences availability of two different CD20 mAbs, rituximab and obinutuzumab, in NHL patients. It was proposed that the standard dose given may not reach su cient therapeutic levels of mAbs in cases with high tumor burden [23,1,25]. Reduction of tRLU or tTAD with increasing tumor burden were not demonstrated in our study.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Recent PK studies have reported that tumor burden in uences availability of two different CD20 mAbs, rituximab and obinutuzumab, in NHL patients. It was proposed that the standard dose given may not reach su cient therapeutic levels of mAbs in cases with high tumor burden [23,1,25]. Reduction of tRLU or tTAD with increasing tumor burden were not demonstrated in our study.…”
Section: Discussioncontrasting
confidence: 70%
“…Patient weight and BSA are parameters which may affect biodistribution of pharmaceuticals as proposed by PK studies [22][23][24][25]. Our analysis did not show any correlations between neither patient weight nor BSA versus tTAD dosage (p = .34 and p = .50 respectively), and activity concentration in tumor (tRLU dosage /volume) (p = .59 and p = .66, respectively).…”
Section: Statisticscontrasting
confidence: 49%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first population PK model for rituximab in pediatric patients with FRNS/SDNS. Thirteen PK models of rituximab have been reported in different disease populations: in patients with NHL ( Regazzi et al, 2005 ; Blasco et al, 2009 ; Müller et al, 2012 ; Gota et al, 2016 ; Tout et al, 2017a ; Rozman et al, 2017 ; Candelaria et al, 2018 ; Ternant et al, 2019 ), in patients with chronic lymphocytic leukemia (CLL) ( Li et al, 2012 ; Tout et al, 2017b ), in patients with rheumatoid arthritis ( Ng et al, 2005 ; Lioger et al, 2017 ) and in patients under plasmapherisis ( Puisset et al, 2013 ). Among these studies, rituximab PK was described as a two-compartment model ( Ng et al, 2005 ; Regazzi et al, 2005 ; Blasco et al, 2009 ; Li et al, 2012 ; Müller et al, 2012 ; Puisset et al, 2013 ; Gota et al, 2016 ; Tout et al, 2017a ; Tout et al, 2017b ; Lioger et al, 2017 ; Rozman et al, 2017 ; Candelaria et al, 2018 ; Ternant et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic disease‐drug interactions are more common for biologic drugs. Examples include target‐mediated drug disposition (TMDD) that is quantitatively modulated by exposure of the biological target correlated to disease load 3 …”
mentioning
confidence: 99%